Endovascular myocardial revascularization in patients with multivessel coronary artery disease with chronic total occlusion and high surgical risk - D. K. Vasiliev (Кардиоваскулярная терапия и профилактика, 2020)
The main reason  for incomplete myocardial revascularization is the presence of chronic coronary total occlusion (CTO), which is detected in every fourth patient during coronary angiography. At the same time, a generally accepted approach  to the treatment of CTO has not yet been developed.Aim. To assess the rationale of complete myocardial revascularization in patients with multivessel coronary artery disease  (CAD) with chronic total occlusion and high surgical risk.Material and methods. This retrospective,  open-label,  non-randomized clinical trial was carried out included 180 patients multivessel CAD and CTO. The patients  underwent endovascular  surgery for complete myocardial revascularization. Depending on the success of surgery, the patients were divided into groups of complete and incomplete myocardial revascularization. Endpoints were death, acute coronary syndrome, re-revascularization after 1-year follow-up. Left ventricular (LV) contractility and clinical status  of patients  in the study groups after 1 year of observation was assessed.Results. The median follow-up was 12,1 months. The successful  rate of revascularization was 79,4%. The incidence of main composite endpoint in the group of complete myocardial revascularization was 5,59%, while in the group of incomplete revascularizations — 21,6% (p=0,005).Conclusion. The study showed  that low incidence  of intraoperative complications and a high successful  rate of revascularization are characteristic of complete myocardial revascularization in patients at high surgical risk with multivessel CAD and CTO. Complete myocardial revascularization leads to a significant decrease in the incidence of major coronary events.